4-Octyl itaconate attenuates LPS-induced acute kidney injury by activating Nrf2 and inhibiting STAT3 signaling - Lujun Xu; Juan Cai; Chenrui Li; Ming Yang; Tongyue Duan; Qing Zhao; Yiyun Xi; Liya Sun; Liyu He; Chengyuan Tang; Lin Sun (BMC, 2023)
Abstract Background Septic acute kidney injury (S-AKI) is the leading form of acute kidney failure among hospitalized patients, and the inflammatory response is involved in this process. 4-octyl itaconate (4-OI) is a multi-target itaconate derivative with potent anti-inflammatory action. However, it remains elusive whether and how 4-OI contributes to the regulation of S-AKI. Methods We employed a lipopolysaccharide (LPS)-induced AKI murine model and explored the potential renoprotective effect of 4-OI in vivo. In vitro experiments, BUMPT cells, a murine renal tubular cell line, were conducted to examine the effects of 4-OI on inflammation, oxidative stress, and mitophagy. Moreover, STAT3 plasmid was transfected in BUMPT cells to investigate the role of STAT3 signaling in the 4-OI-administrated state. Results We demonstrate that 4-OI protects against S-AKI through suppressing inflammation and oxidative stress and enhancing mitophagy. 4-OI significantly reduced the levels of Scr, BUN, Ngal as well as the tubular injury in LPS-induced AKI mice. 4-OI restrained inflammation by reducing macrophage infiltration and suppressing the expression of IL-1β and NLRP3 in the septic kidney. 4-OI also reduced ROS levels, as well as cleaved caspase-3 and boosted antioxidants such as HO-1, and NQO1 in mice. In addition, the 4-OI treatment significantly promoted mitophagy. Mechanistically, 4-OI activated Nrf2 signaling and suppressed phosphorylated STAT3 in vivo and vitro. Molecular docking revealed the binding affinity of 4-OI towards STAT3. ML385, a specific Nrf2 inhibitor, partially repressed the anti-inflammatory and anti-oxidative effects of 4-OI and partially restricted the mitophagy induced by 4-OI in vivo and in  vitro. Transfected with STAT3 plasmid partially suppressed mitophagy and the anti-inflammatory effect provoked by 4-OI in vitro. Conclusion These data suggest that 4-OI ameliorates LPS-induced AKI by suppressing inflammation and oxidative stress and enhancing mitophagy through the overactivation of the Nrf2 signaling pathway, and inactivation of STAT3. Our study identifies 4-OI as a promising pharmacologic for S-AKI.